The effect of brain-based learning on cognitive motivation and preparation of the experimental devices lab experiment report College of Education students (Journal of the College of Basic Education, 2022)
The current research aims to find out the effect of brain-based learning on cognitive motivation and to prepare a report on the experiments of the practical devices laboratory among the students of the College of Education. In order to achieve the goal of the research, the null hypotheses were formulated and an experiment was conducted that lasted a full semester, which is the second semester. The research community consisted of fourth-stage students in the Department of Physics, College of Education, Al-Mustansiriya University, for the academic year (2012-2013). The research sample was deliberately chosen, and its number was (37) male and female students. Equivalence between the two research groups was confirmed through the variables (age in months, previous information and intelligence). For the research tools, a measure of cognitive motivation was prepared (because there was no suitable measure for the purposes of the research) and an observation form to evaluate the numbers of the experiments report of the devices laboratory.